Ligament Augmentation With Mersilene Tape Reduces the Rates of Proximal Junctional Kyphosis and Failure in Adult Spinal Deformity - Pope Rodnoi; Hai Le; Luke Hiatt; Joseph Wick; Joshua Barber; Yashar Javidan; Rolando Roberto; Eric O. Klineberg (Neurospine, 2021)
Objective To investigate prevention of proximal junctional kyphosis (PJK) and failure (PJF) following adult spinal deformity (ASD) surgery utilizing a novel technique of posterior ligament augmentation with polyester fiber tether. Methods This study evaluated ASD adult patients who underwent posterior decompression and instrumented fusion from the thoracolumbar junction (T9–L1) to the pelvis from 2011–2017. Basic demographic data were obtained. Radiographic outcomes included proximal junctional angle (PJA), sagittal vertical axis, PJK, and PJF. The study population was divided into patients who had ASD surgery with and without ligamentous augmentation. Results A total of 43 subjects were evaluated, including 20 without and 23 with ligamentous augmentation. PJA increased over time for both groups. PJA was smaller for the augmented group, and rate of increase in PJA was slower in the augmented group (p<0.0001). The rate of PJK was significantly higher in the nonaugmented group (p=0.01). PJF was significantly less common in the augmented group (p=0.003). Time to revision surgery was lower in the nonaugmented group (p=0.003). Conclusion Our novel ligament augmentation technique utilizing polyethylene tape is an effective technique to slow progression of the PJA and lower the risk for proximal junctional disease in ASD surgery.